Incidence and Outcome Predictors in the Treatment of In-Stent Restenosis with Drug-Eluting Ballons - Aftab Ahmed Solangi, Nasrullah, Amir Jamil, Muhammad Tahir, Jalaludin, Khurshid Ali, (Pakistan Journal of Medical & Health Sciences, 2022)
Background and Aim: In-stent restenosis (ISR) in coronary artery disease patients can be effectively treated with drug-eluting ballons (DEB). Yet, the prevalence and binary restenosis related factors have not been assessed in the past. The present study intended to determine the incidence and outcome predictors in drug-eluting ballons treatment of in-stent restenosis. Methods: This retrospective study was carried out on 152 coronary artery disease patients in Punjab Institute of Cardiology, Lahore from January 2021 to July 2022. Prior to study conduction, the research and ethical committees approved the procedure. Patient’s demographic details, clinical characteristics, laboratory tests, and lesion features were recorded. Data analysis was done in SPSS version 26. Results: Of the total CAD patients, 110 (72.4%) were male and 42 (27.6%) were females. The overall mean age was 56.82±4.56 years. The prevalence of different risk factors for cardiovascular disease such as diabetes, hypertension, smoking, LDL >1.40 mmol/l, and family history was 82 (53.9%), 94 (61.8%), 92 (60.5%), 64 (42.1%), and 16 (10.5%) respectively. Other comorbidities such as chronic kidney disease and heart failure were present in 58 (38.2%) and 12 (7.9%) respectively. High-dose statin therapy was given to 40 (26.3%) patients. The occurrence of MACEs, myocardial infarction, targeted vessel revascularization (TVR), and target lesion revascularization (TLR) during follow-up was 56 (36.8%), 40 (26.3%), 10 (6.6%), and 33 (21.7%) respectively. The mortality rate was 13 (8.6%). Multivariate logistic regression were used to identify the independent factors such as diffuse ISR [OR=2.21: CI 95%, (1.2-1.76), stents ≥2 per lesion [OR=1.78; 95% CI (1.12-2.19)], proximal left anterior descending artery [OR=1.31; 95% CI (1.2-1.76)], and triple vessel disease [OR=2.87, 95% CI (1.1-6.3), p=0.005)]. Conclusion: The present study concluded that In-stent restenosis is a coronary angioplasty serious complication with adverse outcomes. For in-stent restenosis, drug-eluting balloons are an effective alternative to stenting. MACE was shown to be prevalent in our data. MACE is a measure of all-cause mortality in a high-risk group and demonstrates that DEB provides both short-term and long-term advantages in ISR. Keywords: In-stent restenosis, Drug-eluting ballons, Predictor outcomes.